2017
DOI: 10.1074/jbc.m117.801795
|View full text |Cite
|
Sign up to set email alerts
|

Matriptase-2 suppresses hepcidin expression by cleaving multiple components of the hepcidin induction pathway

Abstract: Systemic iron homeostasis is maintained by regulation of iron absorption in the duodenum, iron recycling from erythrocytes, and iron mobilization from the liver and is controlled by the hepatic hormone hepcidin. Hepcidin expression is induced via the bone morphogenetic protein (BMP) signaling pathway that preferentially uses two type I (ALK2 and ALK3) and two type II (ActRIIA and BMPR2) BMP receptors. Hemojuvelin (HJV), HFE, and transferrin receptor-2 (TfR2) facilitate this process presumably by forming a plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 61 publications
7
65
0
1
Order By: Relevance
“…We sought to explore the functions of the noncatalytic domains of MT2 by using cultured cells and MT2 Ϫ/Ϫ mice as models. We previously showed that MT2 cleaves multiple components of the hepcidin-induction pathway (9). Our pilot studies on two other membrane-anchored serine proteases, matriptase and prostasin, strongly indicated the critical roles of the nonproteolytic sequence of MT2 in the specific and efficient cleavage of substrates.…”
Section: The Stem Region Of Mt2 Is Required For An Efficient Cleavagementioning
confidence: 73%
See 2 more Smart Citations
“…We sought to explore the functions of the noncatalytic domains of MT2 by using cultured cells and MT2 Ϫ/Ϫ mice as models. We previously showed that MT2 cleaves multiple components of the hepcidin-induction pathway (9). Our pilot studies on two other membrane-anchored serine proteases, matriptase and prostasin, strongly indicated the critical roles of the nonproteolytic sequence of MT2 in the specific and efficient cleavage of substrates.…”
Section: The Stem Region Of Mt2 Is Required For An Efficient Cleavagementioning
confidence: 73%
“…Early studies suggested that MT2 suppresses hepcidin expression solely by cleaving HJV (8,25). Our recent data showed that MT2 suppresses hepcidin expression independently of Hjv in vivo and that it cleaves multiple components of the hepcidin-induction pathway, including BMP receptors (ALK2, ALK3, ActRIIA, and Bmpr2), Hfe, and to a lesser extent, Hjv and Tfr2, in vitro (9). Consistent with these latter observations, MT2 Ϫ/Ϫ mice have a lower, rather than higher, level of Hjv protein in the liver (26,27).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…In hepatocytes, it has been well‐documented that inflammation induces hepcidin gene expression via the interleukin‐6 (IL‐6)/signal transducer and activator of transcription 3 (STAT3) pathway, via iron sensing through the transferrin receptor 2 (TfR2)/human hemochromatosis protein (HFE), and the bone morphogenetic protein (BMP)/hemojuvelin (HJV)/SMAD (a small mothers of decapentaplegic protein) pathways, and downregulated by erythroferrone (ERFE) ‐dependent and ‐independent mechanisms . Recent studies have also demonstrated that hepcidin expression can be upregulated by progesterone and mifepristone, two steroid hormones, through cell surface protein progesterone receptor membrane component‐1, transforming growth factor β1, SMAD1/5/8‐independent signaling by activin B, oxidases such as NADPH‐dependent oxidase 4 or artificially overexpressed urate oxidase (UOX), IL‐1β via inducing CCAAT enhancer‐binding protein δ (C/EBPδ) expression, peroxiredoxin‐2 which is a supporter for STAT3 transcriptional activity, fibroblast growth factor‐encoding gene, and downregulated by the immunophilin FKBP12 (FK506‐binding protein 1A) via binding with BMP type I receptor ALK2, cystathionine β‐synthase, TfR1, and matriptase‐2 …”
Section: Hepcidin and The Treatment Of Neurodegenerative Disordersmentioning
confidence: 99%
“…Whether HFE-TfR2 complex or HFE in complex with another protein initiates a signaling cascade to induce hepcidin expression is controversial. Signaling then decreases both passively with falling Tf iron saturation and actively through cleavage from the protease matriptase-2 12 . These hypothetical iron-sensing mechanisms are supported by multiple in vitro and in vivo experiments, but mechanisms remain unknown.…”
Section: Introductionmentioning
confidence: 99%